Ectopic Kidney with an Ectopic Ureter Masquerading Adnexal Mass: A Case Report and Literature Review - Li B; Zhu T; Ma F; Zhao Y (Dove Medical Press, 2024)
Boning Li,1,* Tingting Zhu,1,* Fenghua Ma,2 Yuqing Zhao1 1Department of Gynecology, the Obstetrics and Gynecology Hospital of Fudan University, Shanghai, People's Republic of China; 2Department of Radiology, the Obstetrics and Gynecology Hospital of Fudan University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuqing Zhao, Department of Gynecology, the Obstetrics and Gynecology Hospital of Fudan University, No. 128, Shenyang Road, Yangpu District, Shanghai, 200090, People's Republic of China, Tel +86-13817678883, Fax +86-021-33189900, Email yyqingzz@126.comAbstract: An ectopic kidney is a rare congenital defect that is often asymptomatic, but can be incidentally discovered during imaging examinations. Moreover, the morphological characteristics and laboratory features of ectopic kidneys are nonspecific, which may lead to misleading diagnostic approaches, particularly when there are additional factors, such as infection, obstruction, or other anomalies. A 43-year-old female presented with a mass in the left adnexal area. She had septate uterus and a history of congenital urinary incontinence. Ultrasound and MRI findings indicated that the mass was a cyst originating from the ovary. However, it is possible that the lump was derived from the urinary system. To confirm the diagnosis, laparoscopy was performed, followed by pathological examination, which confirmed the presence of an ectopic kidney with a single-system ectopic ureter. The patient underwent nephroureterectomy, and her symptoms successfully resolved, leading to a favorable prognosis. This case report highlights a rare case involving an ectopic kidney with a vaginal ectopic ureter that initially presented as an adnexal cyst and caused urinary dribbling. This case emphasizes the importance of early recognition and accurate diagnosis in women with similar symptoms.Keywords: ectopic kidney, ectopic ureter, urinary incontinence, pelvic mass, urogenital malformation